Workshop Penguatan Kemampuan Guru dalam Penelitian Tindakan Kelas dan Menulis Karya Ilmiah Berbasis Teknologi di SD Ummu Aiman Lawang: Workshop on Strengthening Teachers Abilities in Classroom Action Research and Writing Technology-Based Scientific Papers at Ummu Aiman Lawang Elementary School - Zulkarnain, Wildan; Prestiadi, Dedi; Nurabadi, Ahmad; Sunarni, Sunarni; Masytho, Asri; Ubaidillah, Endra; Putri, Septiani Cahyaning; Arrahmah, Olivia Vieca; Subkhan, Muhammad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Classroom Action Research (CAR) is one of the important activities carried out by teachers to improve the quality of learning. Through CAR activities, teachers can analyze the problems experienced during learning. In addition to CAR, teachers are also expected to be able to carry out publication activities on the results of CAR that have been implemented. With the advancement of technology, it is also expected that teachers will find it easier to compile scientific papers. This Community Service Activity aims to reinforce teachers in implementing CAR and writing scientific papers based on technology. This Community Service Activity was carried out at Ummu Aiman Lawang Elementary School, Malang Regency. The targets of this community service are Class Teachers and Subject Teachers at Ummu Aiman Lawang Elementary School. This activity was carried out using the discussion and question-and-answer method. The results of this community service are an increase in teacher understanding of CAR activities and the use of technology to support publication. This result was obtained from the analysis of the achievement of community service activities seen from the post-test score where participants experienced an increase in understanding with an average value of 83.75.